2016
DOI: 10.21608/ejabf.2016.11175
|View full text |Cite
|
Sign up to set email alerts
|

Nesting activities of Green turtles (Chelonia mydas) on the beaches of Zabargad Island, southern Egyptian Red Sea

Abstract: Nesting of green turtles Chelonia mydas on the most valuable nesting of Zabaragad Island beaches were studied during the period between 2009 and 2014. On annual basis, and during the peak of the nesting season (mid of July), the nesting beaches on Zabargad Island were surveyed to estimate dimensions of female tracks, nests and female sizes and numbers of female tracks and true and false nests per night. Based on the model (software R) created by Girondot et al. (2012), the total numbers of tracks per season we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Medium levels of nesting green turtles have been recorded on the Gulf side of Saudi Arabia (800) (Pilcher 2000, Pilcher & Al Merghani 2000 and the Red Sea coast (400) (Shimada et al 2021b). Lower levels of nesting have been reported from Djibouti, Egypt, Somalia, and Sudan (40−250) (PERSGA/GEF 2003, PERSGA 2006, El-Sadek et al 2016, Nasr 2015 unpubl. data).…”
Section: Estimated Magnitude Of Nestingmentioning
confidence: 99%
“…Medium levels of nesting green turtles have been recorded on the Gulf side of Saudi Arabia (800) (Pilcher 2000, Pilcher & Al Merghani 2000 and the Red Sea coast (400) (Shimada et al 2021b). Lower levels of nesting have been reported from Djibouti, Egypt, Somalia, and Sudan (40−250) (PERSGA/GEF 2003, PERSGA 2006, El-Sadek et al 2016, Nasr 2015 unpubl. data).…”
Section: Estimated Magnitude Of Nestingmentioning
confidence: 99%
“…Few studies on marine turtles in the Red Sea were reported, where the first review was presented by Frazier and Salas (1984) followed by Moschis, 1985;Frazier et al, (1987); Mortimer, 1990;IUCN/UNEP, 1996;Laurent et al, 1996 and1998;Torok, 1997;Venizelos and Kallonas, 1999;Foley et al, 2006;Fadini et al, 2011;Péron et al, 2013;and Mancini et al, 2015. Also, recent studies on marine turtles of the Egyptian Red Sea was presented by Hanafy and Sallam, 2003;PERSGA/GEF, 2004;Hanafy, 2012;El-Sadek et al, 2013 andAttum et al, 2014). Therefore,this work aimsto throw the light on the Sedimentary characteristics and their effects on nestingpopulation.…”
Section: Introductionmentioning
confidence: 99%